Penilaian Persediaan Menurut Pernyataan Standar Akutansi Keuangan (PSAK) dan Undang-undang Pajak - Widjaja, Siana Murti (LAW REVIEW, 2002)
Indonesian Accounting Standard requires that an asset be reported in the financial  statements at the lower of its historical cost or its net realizable value. Inventories are  normally accounted for at historical cost, as the cost principle requires. But if the net  realizable value of inventory falls below its historical cost, then the accountants must  write down the value of its goods. The accountants report ending inventory at its Lower  of cost or net realizable value. The lower of cost or net realizable value rule shows accounting conservatism in action. Conservatism appears in accounting guidelines like "anticipate no gains, but provide for all probable losses" and "if doubt, record an asset at the lowest reasonable amount and a liability at the highest reasonable amount". Conservatism also directs accountants to decrease the accounting value of an asset if it appears unrealistically high, even if no transaction occurs. Inventory cost is the price the business pays to acquire the inventory, not the selling price of the goods. Inventory cost includes its invoice price, less any purchase discount, plus tariffs, transportation charges, insurance while in transit, and all other costs incurred to make the goods ready for sale. Determining the unit cost of inventory is easy when the unit cost remains constant during the period. However, the unit cost often changes. For example, during times of inflation, prices rise. To compute the cost of goods sold and ending inventory amounts, the accountant must have some means of assigning the businesss cost to each item sold. The four costing methods that Indonesian Accounting Standard allows are: 1. Specific unit cost.  2. Weighted avarage cost. 3. First-in, first out (FIFO) cost. 4. Last-in, first-out (LIFO) cost.